Strategic planning features of subsurface management in Kemerovo Oblast - Romanyuk V. B. Vera Borisovna; Grinkevich A. M. Anastasiya Mikhailovna; Akhmadeev K.; Pozdeeva G. P. Galina Petrovna (Petroleum Engineering Economics and Mining Law, 2016)
Title screen